The new Sonoma diet : a simple, healthy, more delicious way to live : trimmer waist, more energy in just 10 days - Guttersen, Connie (New York : Sterling, 2010)
'From the vibrant California valley where healthy eating and active lifestyles are a way of life comes'The New Sonoma diet', the completely updated and improved version of a weight loss plan like no other...'--Dust jacket flap.
'Completely updated & simplified with new power foods'--Dust cover.
Includes bibliographical references (p. 366-368) and indexes.
Keywords: Reducing diets; Reducing diets -- Recipes; Nutrition